Research and Design on Navigation Electronic Map System - Wanwu Li Wanwu Li; Lin Liu; Honglei Dai; Chang Qu Chang Qu; Xiaotong Yang (Universitas Ahmad Dahlan, 2013)
This paper puts forward the new definition on the basis of the original concept of the navigation electronic map, designs the structure of the navigation electronic map system which contains three parts: hardware equipment, data system and software system, and analyzes each part of them in detail, finally this paper discusses the functional framework of the navigation electronic map.